The Correlation between Junk Food Consumption and Age of Menarche of Elementary School Student In Gedung Johor Medan - Anita, Surya; Simanjuntak, Yunida Turisna (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2018)
ABSTRACT Acceleration age of menarche, can increase the chances of endometrial hyperplasia. The incidence of uterine and breast cancer are associated with early menarche. Junk food is indicated as one of the triggers of early menarche. With observational-analytic research and case-control research design, it was conducted to determine the effect of junk food in early menarche at elementary school student. The population of the study was the 6th grade elementary school students who had been menstruated, yet the sample was chosen randomly. Data collected using questionnaires, also measuring weight and height, then analysed using chi-square. The results shows a relationship between junk food consumption with early menarche incidence (p = 0.021) and OR 1.889. This is due to the high consumption patterns of junk food/fast food in teenages. Affected by behavioral patterns of people who tend to choose practical food, easy to get and ready to eat.   ABSTRAK Percepatan usia menarche dapat memperbesar peluang terjadI hyperplasia endometrium. Insiden kanker uterus dan kanker payudara dihubungkan dengan menarche dini.  Junk food diindikasi sebagai salah satu pemicu menarche dini. Dengan penelitian observasional-analitik dan desain penelitian case-control, dilakukan untuk mengetahui pengaruh junk food pada menarche dini di usia SD. Populasi penelitian adalah siswi SD kelas VI yang sudah haid /belum, sampel dipilih secara random. Pengumpulan data menggunakan kuesioner kepada siswi, menimbang berat badan serta  mengukur tinggi badan. Analisis data menggunakan chi-square. Hasil penelitian bahwa ada hubungan konsumsi junk food dengan kejadian menarche dini (p=0,021) dan OR 1,889. Hal ini disebabkan Tingginya pola konsumsi junk food/fast food  pada remaja dipengaruhi oleh pola perilaku masyarakat yang cenderung memilih makanan praktis, mudah didapat dan siap saji.